2004
DOI: 10.1308/003588404322827518
|View full text |Cite
|
Sign up to set email alerts
|

Hip osteoarthritis: where is the pain?

Abstract: Hip pain referred below the knee is common with a degenerate hip joint and follows the distribution of the saphenous nerve, which branches from the femoral nerve. Radiographic deterioration of a hip joint does not correlate with pain distribution or patient dysfunction as measured by the Oxford Hip Score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
73
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 3 publications
0
73
0
1
Order By: Relevance
“…Our observations suggest 55% of our patients undergoing hip arthroplasties had IKP, which was high compared with 17.6% for the contralateral knee. Khan et al [21] suggested a similar phenomenon with 68.6% and 50.9% of patients scheduled to undergo hip arthroplasties reporting anterior and posterior knee pain, respectively, before surgery. Although IKP is frequent in patients with severe hip disease, the direct cause remains unknown.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Our observations suggest 55% of our patients undergoing hip arthroplasties had IKP, which was high compared with 17.6% for the contralateral knee. Khan et al [21] suggested a similar phenomenon with 68.6% and 50.9% of patients scheduled to undergo hip arthroplasties reporting anterior and posterior knee pain, respectively, before surgery. Although IKP is frequent in patients with severe hip disease, the direct cause remains unknown.…”
Section: Discussionmentioning
confidence: 87%
“…Most previous studies have been case reports [8, 10-13, 15, 16]. Only several observational reports describe the distribution of the referral pain of hip disease [21,24,32]. We therefore asked: (1) if hip disease was associated with preoperative IKP and (2) does IKP improve after hip arthroplasty?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24,42 This is more common in adolescents. In adults, the presence of knee pain without concurrent complaints from the hip is not seen as often.…”
mentioning
confidence: 99%